2016
DOI: 10.1186/s12864-015-1920-7
|View full text |Cite
|
Sign up to set email alerts
|

Subtelomere organization in the genome of the microsporidian Encephalitozoon cuniculi: patterns of repeated sequences and physicochemical signatures

Abstract: BackgroundThe microsporidian Encephalitozoon cuniculi is an obligate intracellular eukaryotic pathogen with a small nuclear genome (2.9 Mbp) consisting of 11 chromosomes. Although each chromosome end is known to contain a single rDNA unit, the incomplete assembly of subtelomeric regions following sequencing of the genome identified only 3 of the 22 expected rDNA units. While chromosome end assembly remains a difficult process in most eukaryotic genomes, it is of significant importance for pathogens because the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 80 publications
(80 reference statements)
1
12
0
Order By: Relevance
“…The InterAE, B, C and D predicted proteins accounted for a total of 50.0, 35.5 and 32.4% of the E. intestinalis , E. hellem and E. cuniculi predicted subtelomere ORFs, respectively, and several of the repeated InterC and InterD proteins appeared unique to E. hellem and E. intestinalis , suggesting that their genes were duplicated post-speciation (Table S 3 ). Albeit putative functions could not be inferred for these proteins, predictive folding revealed that members of the InterC and InterD families harbor alpha-helical structures common to transmembrane proteins, congruent with previous observations [ 9 ], and corroborated by deep-learning inferences based on sequence data (Fig. 3 ).…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…The InterAE, B, C and D predicted proteins accounted for a total of 50.0, 35.5 and 32.4% of the E. intestinalis , E. hellem and E. cuniculi predicted subtelomere ORFs, respectively, and several of the repeated InterC and InterD proteins appeared unique to E. hellem and E. intestinalis , suggesting that their genes were duplicated post-speciation (Table S 3 ). Albeit putative functions could not be inferred for these proteins, predictive folding revealed that members of the InterC and InterD families harbor alpha-helical structures common to transmembrane proteins, congruent with previous observations [ 9 ], and corroborated by deep-learning inferences based on sequence data (Fig. 3 ).…”
Section: Resultssupporting
confidence: 88%
“…Of these, only 34.5% (60/174) of the ORFs predicted in the E. intestinalis subtelomeres were found shared with both E. hellem and E. cuniculi , many of which as part of large repetitive families. E. cuniculi was previously shown to harbor repetitive gene families known as interAE , interB , interC and interD in its subtelomeres [ 9 , 32 ], and those were found in all three Encephalitozoon species, albeit in different copy numbers. The InterAE, B, C and D predicted proteins accounted for a total of 50.0, 35.5 and 32.4% of the E. intestinalis , E. hellem and E. cuniculi predicted subtelomere ORFs, respectively, and several of the repeated InterC and InterD proteins appeared unique to E. hellem and E. intestinalis , suggesting that their genes were duplicated post-speciation (Table S 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations